Phylogenetic morphometrics, geometric morphometrics and the Mexican fossils to understand evolutionary trends of enchodontid fishes. (November 2021) - Díaz-Cruz, Jesús Alberto; Alvarado-Ortega, Jesús; Ramírez-Sánchez, Marcia M.; Bernard, Emma Louise; Allington-Jones, Lu; Graham, Mark
Abstract: Enchodontids were a diverse and abundant fish marine clade that during the Upper Cretaceous became common inhabitants of temperate coastal environments around the world. The recent studies on Mexican enchodontid species have contributed to better understand their evolutionary relationships; however, the phylogenetic significance of the morphological variability of some bones in these fishes is unclear. Here, we explore the morphological variation and the phylogenetic implications that the preopercle, and lower jaw have throughout the geological time; these bones were selected because usually are well-preserved in fossils belonging to the group. Our results indicate that temporally, the enchodontid species herein studied can be divided into two main groups, one present in the early-Upper Cretaceous group and the other in the late-Upper Cretaceous. Additionally, our results indicate that body size in Enchodontidae seems to adjust to the phyletic increase of size or Cope's rule. The shapes of the preopercle and lower jaw of enchodontids are highly variable that it is hard to use these as supra-specific distinctive features. Among these fishes, the most differentiated shapes correspond to those that developed an elongated and shallow lower jaw, and those with preopercles that bear a posteroventral well-developed spine, as in Eurypholinae and Unicachichthys . The phylogenetic relationships of enchodontid fishes defined by the configurations of these two skeletal structures provide a glimpse of the biogeographical relationships of the family; however, these patterns should be analyzed considering a most complete and inclusive phylogeny. Highlights: Geometric Morphometrics and Phylogenetic Morphometrics analyses are performed on highly variables structures of enchodontids. A particular bone-shape is hardly diagnostic of any genus of Enchodontidae. Corporal size in enchodontids apparently fit the Cope's rule. The Hispanic corridor is crucial for understand the enchodontid interchange and occupation of the different Tethys realms.